Jessica, the Heiress - Raymond, Evelyn, 1843-1910 (Salt Lake City, UT : Project Gutenberg, 2009)
"Jessica, the Heiress" by Evelyn Raymond is a novel written in the early 20th century. The story centers on Jessica Trent, a young heiress who becomes embroiled in a mystery after her sudden disappearance triggers concern and anxiety among her family and friends. The narrative unfolds primarily at the Sobrante ranch, where the interactions between Jessica, her Aunt Sally, and various ranch hands set the stage for an exploration of themes such as family loyalty, resilience, and the quest for truth. The opening of the book establishes an idyllic yet suspenseful atmosphere, showcasing Jessica$1 (Bs leisurely morning with Aunt Sally on the ranch. Their light-hearted banter is sharply contrasted by the gravity of Jessica's mysterious absence soon after, which plunges her mother and others into a state of worry and fear. As they react to her disappearance, the narrative introduces a sense of urgency and danger, foreshadowing complications that arise from hidden secrets and familial obligations. The interactions hint at a tightly-knit community that will band together to search for Jessica, igniting a deeper mystery about her fate and the dynamics at play within the ranch. (This is an automatically generated summary.)s
Release date is 2009-09-24
E-text prepared by Roger Frank and the Project Gutenberg Online Distributed Proofreading Team (http://www.pgdp.net)
Keywords: Fiction